Development and global governance : conference proceedings, May 2, 1995, Ottawa, Canada - Culpeper, Roy, 1947-; Pestieau, Caroline, 1940- (International Development Research Centre : North-South Institute, 1996)
Fifty years on, the reform of the Bretton Woods institutions -- the World Bank and the International Monetary Fund -- has become a lively issue. The G-7 industrialized countries took a first bite at this subject during their Halifax Summit, and the debate continues. A group of experts from all continents met in Ottawa to give challenging advice to the summiteers and beyond, ranging from the view that the G-7 itself is in eclipse to an argument for turning the IMF into a central world bank. This book contains the seven papers and a summary of the discussion from that meeting, sponsored jointly by the International Development Research Centre and the North-South Institute.